Interdependent response of three critical infrastructures in a South American megacity - Cárdenas-Mamani, Ú.; Kahhat, R.; Magallanes, J.M. (Institute of Physics, 2022)
Critical infrastructures (CIs) are key for the functionality of urban areas. Their failure due to natural disasters or manmade disruptive events could severely obstruct normal city activities, producing considerable social and economic impacts. Understanding CI performance and interdependence during these events is imperative. This study aims to comprehend the independent and interdependent response of three CIs in a South American megacity: Lima, Peru. Topological indicators were used to study three CIs: potable water distribution, electricity distribution and natural gas distribution; five disruption scenarios were modeled. Results show that, compared to the other CIs, the potable water system has the highest redundancy, while the electricity network has the best capacity to connect among all elements. The structure of the natural gas system makes it fragile and susceptible to failures, generating the lowest values across indicators. Regarding the interdependence analysis, certain elements (e.g., medium- and high-voltage substations, water treatment plant, pressure stations) with a high degree of connectivity influence the entire performance of the systems; the interdependent effect exposes some CIs to damage more than others. Earthquakes have a comparatively more negative impact on the CIs studied than manmade disruptive events. In order to reduce vulnerability factors in the three systems, an important mitigation action would be to reduce the centralization of the systems.
Keywords: Critical infrastructures; Interdependence analysis; Disruption scenarios; https://purl.org/pe-repo/ocde/ford#1.03.00